PENUNDAAN PEMBAYARAN KLAIM JAMINAN KESEHATAN NASIONAL OLEH BPJS KESEHATAN DI INDONESIA: SEBUAH SCOPING REVIEW - Tarigan, Immanuel Natanael; Lestari, Feni Dwi (Jurnal Ekonomi Kesehatan Indonesia, 2022)
Since it was first implemented, the utilization of the National Health Insurance (JKN) has been increasing each year. Currently, almost all hospitals accept JKN patients. However, the JKN claim payment process did not run as conveniently as expected, and there were frequent delays in payment. This delay becomes a major obstacle in hospitals, especially public hospital, which relies heavily upon JKN patients for its cashflow. This study aims to determine the magnitude of the delay in the payment of JKN claims and what factors are involved, especially in public hospitals. This study was conducted using the scoping method review with Arksey and O'Malley guidelines. The study was conducted by including publications from 2014 to 2022. A literature search was carried out on 3 electronic databases and additional searches, found a total of 530 articles. A total of 35 studies were analyzed in this study. This study found that the delay in the payment of JKN patient claims was around 2.5-47.7% per month. Several factors that were found to be closely related to the delay in payment of this claim were administrative completeness, the number of staff involved, the ability and accuracy of the coder, the completeness of the medical resume by the doctor in charge of the patient, good communication between the doctor in charge of the patient and coder, the use of internal verifiers, facility support. and infrastructure as well as the existence of standard operating procedures.